Research Progress of Self-Powered Gait Monitoring Sensor Based on Triboelectric Nanogenerator - Yupeng Mao; Jiaxiang Liang; Rui Zhang; Tianming Zhao; Aiguo Zhou (Applied Sciences)
In recent years, technologies in the field of gait monitoring, such as gait parameter analysis, health monitoring, and medical diagnosis, have become increasingly mature. Gait monitoring technology has emerged as an effective means for disease prevention and diagnosis. Triboelectric nanogenerator technology not only overcomes the limitations of relying on external power sources and frequent battery replacements but also offers advantages such as low cost, lightweight, a wide range of material options, and ease of manufacturing. This review introduces the common working modes of triboelectric nanogenerators and summarizes recent advances in self-powered gait monitoring applications (e.g., gait analysis, fall detection, rehabilitation assessment, and identity recognition), and highlights persistent challenges such as wearability, washability of fabric-based devices, reliability, system integration, and miniaturization, along with proposed solutions.